The influence of social capital on technology transfer performance: an investigation in high technology companies - Abidin, Rahimi; Jusoh, Muhammad Shahar; Amlus, Mohamad Harith; Osman, A. (AENSI, 2014)
Background: Social interaction is very important to facilitate technology transfer among the units within an organization.The prominent concept that provides a foundation to explain the properties of relations between the units is social capital.Using the data from a survey on industrial firms in the technology parks in Malaysia, this paper provides an investigation on the relationship between three dimensions of internal social capital and technology transfer performance, within the technology park incubating company setting.The finding indicated that each dimension of social capital has positive and significant relationship with technology transfer performance.